ANALISIS HADIS-HADIS TENTANG MUSIK - Siregar, Dame (AIN Padangsidimpuan, 2016)
The music of rebana is very popular all mankind irrespective of differences of religion. Even the music is to alienate Muslims from Islam in terms of study, live, teach, pinning and put it into practice. Besides, Muslims confounds during informal atmosphere with music and singing so ta'lim is just mere masks with a slogan for the Islamization of music and singing. At the end of study groups has no meaning implicitly and explicitly. The significance of this description is to reveal how it should be music in Islam, both in terms of the shape tools, people who play, the time and place.